2014
DOI: 10.1152/ajpcell.00069.2014
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction meets vesicle traffic: the software and hardware of GLUT4 translocation

Abstract: Skeletal muscle is the major tissue disposing of dietary glucose, a function regulated by insulin-elicited signals that impart mobilization of GLUT4 glucose transporters to the plasma membrane. This phenomenon, also central to adipocyte biology, has been the subject of intense and productive research for decades. We focus on muscle cell studies scrutinizing insulin signals and vesicle traffic in a spatiotemporal manner. Using the analogy of an integrated circuit to approach the intersection between signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 74 publications
3
112
0
5
Order By: Relevance
“…The actin cytoskeleton has been implicated in glucose transport for some time (Klip et al, 2014), and two recent studies have demonstrated that Tpm3.1-containing actin filaments regulate glucose uptake in mice in an isoform-specific manner (Lim et al, 2015;Kee et al, 2015). Here, insulin stimulation of Akt was shown to result in phosphorylation of Tmod3, which caps Tpm3.1-containing actin filaments that are involved in actin reorganization at the cell periphery and increased incorporation of GLUT4 into the plasma membrane (Lim et al, 2015).…”
Section: Metabolismmentioning
confidence: 86%
“…The actin cytoskeleton has been implicated in glucose transport for some time (Klip et al, 2014), and two recent studies have demonstrated that Tpm3.1-containing actin filaments regulate glucose uptake in mice in an isoform-specific manner (Lim et al, 2015;Kee et al, 2015). Here, insulin stimulation of Akt was shown to result in phosphorylation of Tmod3, which caps Tpm3.1-containing actin filaments that are involved in actin reorganization at the cell periphery and increased incorporation of GLUT4 into the plasma membrane (Lim et al, 2015).…”
Section: Metabolismmentioning
confidence: 86%
“…Other signaling pathways, such as PI3K-dependent activation of the exocyst complex (Chen et al, 2011) and atypical protein kinase C pathways (Kanzaki et al, 2004;Liu et al, 2010;Sajan et al, 2014a,b) might be activated in adipocytes, but these have not been well appreciated. Particularly in muscle cells, PI3K stimulates Rac1 signaling, and this is required together with Akt to promote GLUT4 translocation and glucose uptake (Chiu et al, 2011;Klip et al, 2014;Sylow et al, 2014;Ueda et al, 2010). The Rac1 pathway is likely to act in adipocytes as well (Balamatsias et al, 2011;Tsuchiya et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which constitutively active Akt2 has been overexpressed, or in which chemical-genetic approaches have been used to activate Akt2 acutely, suggest that Akt2 alone is fully sufficient to stimulate GLUT4 translocation (Kohn et al, 1996;Ng et al, 2010bNg et al, , 2008. However, comparison of GLUT4 translocation after acute Akt2 activation has been made only upon submaximal insulin stimulation, and it remains unclear how the data fit with the less-well-studied non-PI3K and nonAkt signals that are required for insulin-stimulated GLUT4 translocation Chang et al, 2007;Chiang et al, 2001;Farese et al, 2007;Klip et al, 2014;Sajan et al, 2014b;Sylow et al, 2014;Ueda et al, 2010;Cheney et al, 2011;Govers et al, 2004;Martinez et al, 2010). In particular, although PI3K and Akt are two major signaling nodes in insulin-regulated GLUT4 trafficking, previous studies have not examined the individual contributions of acute activation of each of these kinases separately and have not compared the overall effect with that of maximal insulin stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…37 AS160 is a known regulator of GLUT4 glucose transporter translocation to the PM upon insulin stimulation of fat and muscle cells. 38 Insulin stimulation triggers Akt activation which phosphorylates AS160 leading to its inactivation and binding to 14-3-3 proteins and the consequent activation of Rab 8A and 13 in myocytes, and Rab10 in adipocytes, which then facilitate the targeting of GLUT4-containing vesicles to the cell surface. In CCD cells, Na C transport involves the increased expression of 14-3-3 proteins and their association with the ubiquitin E3 ligase Nedd4-2, a substrate of serum-and glucocorticoidinduced kinase (SGK1).…”
Section: Regulation Of Enac Density At the Cell Surface By Rab Gtpasesmentioning
confidence: 99%